Embriogenesis Somatik Jeruk Keprok (Citrus reticulata L. cv Batu 55) Asal Hasil Perlakuan Kolkisin - Agus Purwito; Mohamad Prayogi; Mia Kosmiatin; Ali Husni (Jurnal Hortikultura Indonesia, 2015)
ABSTRACTThe objective of this study was to obtain the best method of regeneration through somatic embryogenesis of citrus cv Batu 55 from callus resulted from in vitro polyploidization by colchicine. The experiment was conducted at the Laboratory of ICABIOGRAD, Bogor and Tissue Culture Laboratory, Department of Agronomy and Horticulture, Bogor Agricultural University from March 2014 until September 2014. This study consisted of proliferation of embryogenic callus, maturation, germination of somatic embryos, growth of shoots and roots. The research were comprised of four experiments, namely: 1). The effect of Phytagel concentration (2.5, 3.0, 3.5 and 4.0 g L-1) on proliferation of embryogenic callus, with 3 replications. Each experimental unit consisted of 3 clumps of callus, 2). The effect of ABA concentration (0, 0.1, 0.3 and 0.5 mg L-1) on somatic embryo maturation with 6 replications. Each experimental unit was one culture vessel containing five somatic embryos at globular phase, 3) The effect of vitamin composition (vitamin MS and vitamin MW) on germination of somatic embryo with 16 replications. Each experimental unit was one culture vessel containing four somatic embryos at cotyledonary phase, and 4) The effect 0.5 mg L-1 of plant growth regulators (NAA, IAA, IBA) and vitamin (MS and MW) on rooting and shoot elongation of germinated somatic embryos. Experiment was repeated five times. Each experimental unit was one culture vessel containing one plantlet as explant. All experiments were arranged as a completely randomized design. The result showed that the best concentration of Phytagel for callus proliferation was 2.5 g L-1. Maturation of somatic embryos was better when the somatic embryos were planted on medium supplemented with ABA 0.5 mg L-1. The MS medium supplemented with vitamin MS was better than supplemented with vitamin MW for the formation of plantlets, while roots and shoots elongation of the plantlet was better when explant was planted on the MS medium supplemented with vitamins MS and IBA 0.5 mg L-1.Key words: proliferation, maturation, germination, embryogenic callus, plantlet.ABSTRAKPenelitian ini bertujuan untuk mendapatkan metode embriogenesis somatik terbaik dari kalus Jeruk Keprok cv Batu 55 yang mendapatkan perlakuan poliploidisasi dengan kolkisin. Penelitian dilakukan di Laboratorium Balai Besar Litbang Bioteknologi & Sumber Daya Genetik Pertanian, dan Laboratorium Kultur Jaringan, Departemen Agronomi dan Hortikultura, Institut Pertanian Bogor mulai bulan Maret 2014 hingga September 2014. Penelitian ini terdiri atas proliferasi kalus embriogenik, pendewasaan, perkecambahan embrio somatik (ES), pertumbuhan tunas dan akar. Penelitian terdiri atas empat percobaan, yaitu: 1). Pengaruh konsentrasi Phytagel (2.5, 3.0, 3.5 dan 4.0 g L-1) terhadap proliferasi kalus embriogenik, dengan 3 ulangan, dimana setiap satuan percobaan terdiri atas 3 klum kalus, 2). Pengaruh konsentrasi ABA (0, 0.1, 0.3 dan 0.5 mg L-1) terhadap pendewasaan ES dengan 6 ulangan. Setiap satuan percobaan ialah satu botol kultur yang ditanam lima ES fase globular, 3) Pengaruh komposisi vitamin (vitamin MS dan vitamin MW) terhadap perkecambahan ES dengan 16 ulangan. Setiap satuan percobaan ialah satu botol kultur yang ditanami empat ES fase kotiledon, dan 4) Pengaruh 0.5 mg L-1 zat pengatur tumbuh (NAA, IAA, IBA) dan vitamin (MS dan MW) terhadap pertumbuhan tunas dan akar pada ES yang telah berkecambah. Setiap perlakuan diulang lima kali. Setiap satuan percobaan ialah satu botol kultur yang berisi satu planlet. Seluruh percobaan disusun menggunakan rancangan acak lengkap (RAL). Hasil menunjukkan bahwa konsentrasi terbaik Phytagel untuk proliferasi kalus adalah 2.5 g L-1. Pendewasan menjadi ES fase kotiledon akan lebih baik jika ES ditanam pada medium dengan ABA 0.5 mg L-1. Untuk pembentukan planlet, ES fase kotiledon akan lebih baik ditanam dalam medium MS yang ditambah vitamin MS dibanding yang ditanam pada medium MS ditambah vitamin MW. Medium untuk pertumbuhan tunas dan akar terbaik adalah medium MS yang ditambah dengan vitamin MS dan IBA 0.5 mg L-1.Kata kunci: proliferasi, pendewasaan, perkecambahan, kalus embriogenik, planlet.